Regulation of signal transduction cascades by Pterostilbenes in different cancers: Is it a death knell for oncogenic pathways - Butt, Ghazala; Attar, Rukset; Tabassum, Sobia; Aras, Aliye; Qadir, Muhammad Imran; Ozbey, Ulku; Alaaeddine, Nada; Ozcelik, Beraat; Farooqi, Ammad Ahmad (Cellular and Molecular Biology, 2017)
Interdisciplinary research has revolutionized the field of medicine and we have witnessed exponential increase in the high-impact research in past few decades. However, the road to this burgeoning research field is obstacle-ridden because of intratumor heterogeneity, loss of apoptosis and dysregulation of spatio-temporally controlled signaling pathways. Ground-breaking findings obtained through genetic, genomic and proteomic studies have considerably improved our concepts related to the complexity of protein network and excitingly, discovery of miRNAs has added another layer of intricacy to quantitatively regulated gene networks. In this review, we chronicle the milestone achievements and discuss how Pterostilbenes effectively regulated different cellular pathways. We have provided detailed mechanistic insights related to regulation of JAK-STAT signaling, Notch pathway, Wnt mediated intracellular signaling by pterostilbene. Underlying mechanisms about regulation of PI3K/AKT and MAPK pathways by pterostilbene in different cancers. Regulation of Metastasis-associated protein 1 (MTA1) proteins and Human telomerase reverse transcriptase (hTERT) in cancer cells by pterostilbene. Pterostilbene has also been reported to modulate the expression of various oncogenic and tumor suppressor microRNAs in cancer cells. Better and sharper comprehension of the concepts associated with the modes of action of pterostilbene in different cancers will be useful in identification of cancers which can be efficiently targeted by pterostilbene.